The study of operation modes and control strategies of a multidirectional MC for battery based system - Toosi, Saman; Misron, Norhisam; Hanamoto, Tsuyoshi; Aris, Ishak; Mohd Radzi, Mohd Amran; Yamada, Hiroaki (Hindawi Publishing Corporation, 2015)
To enhance the performance of stand-alone battery based system and to achieve the continuous power transmission, the behavior of multidirectional matrix converter (MDMC) has been analyzed in different operation modes. A systematic method interfacing a renewable source, a storage battery, and a load is proposed for a stand-alone battery based power system (SABBPS) to utilize the MDMC as PWM converter, inverter, or PWM converter and inverter in different operation modes. In this study, the Extended Direct Duty Pulse Width Modulation (EDDPWM) technique has been applied to control the power flow path between the renewable source, load, and the battery. Corresponding to generator voltage, input frequency, and loads demands, several operating states and control strategies are possible. Therefore, the boundaries and distribution of operation modes are discussed and illustrated to improve the system performance. The mathematical equation of the EDDPWM under different operation modes has been derived to achieve the maximum voltage ratio in each mode. The theoretical and modulation concepts presented have been verified in simulation using MATLAB and experimental testing. Moreover, the THD, ripple, and power flow direction have been analyzed for output current to investigate the behavior of system in each operation mode.